An Acoustic Survey of Beaked Whales and Kogia spp. in the Mariana Archipelago Using Drifting Recorders - McCullough, Jennifer L. K.; Wren, Johanna L. K.; Oleson, Erin M.; Allen, Ann N.; Siders, Zachary A.; Norris, Erik S. (Frontiers in Marine Science, 2021)
The distribution, abundance, and habitat of cryptic cetacean species such as beaked whales and dwarf/pygmy sperm whales (Kogia spp.) are challenging to study due to their long dive times and/or very limited surface behavior. Even less is known in minimally studied and remote regions, including the Mariana Archipelago and parts of the broader western Pacific. In 2018, we deployed a network of eight Drifting Acoustic Spar Buoy Recorders (DASBRs) on the west side of the Mariana Archipelago with the goal of examining the distribution and habitat of beaked whales and Kogia spp. in this region using passive acoustic monitoring. Concurrently, conductivity-temperature-depth (CTD) data were collected within the drift area and combined with satellite oceanographic data to build Ensemble Random Forest Models to identify specific oceanographic features that determine the distribution of these species. DASBRs deployed at locations ranging from 13°N to 18°N generally drifted from east to west between the Mariana Archipelago and the West Mariana Ridge. Spectral and temporal characteristics of echolocation signals were used to identify the presence of beaked whales and Kogia spp. species. This dataset contained frequency modulated (FM) pulses characteristic of Longman’s (Indopacetus pacificus), Cuvier’s (Ziphius cavirostris), and Blainville’s (Mesoplodon densirostris) beaked whales, as well as the unidentified beaked whale FM pulse known as the “BWC,” along with narrow-band high frequency clicks from Kogia spp. The detection rate was substantially higher for all species on the five tracks in the region north of 15.5°N than for those drifts occurring farther south. Species distribution models suggest that differences in the oceanographic characteristics between the northern and southern regions may impact foraging opportunities, possibly explaining the specific ecological niche for these species within this water mass. This is the first study of the distribution of cryptic cetacean species within the wider Mariana Archipelago region. We demonstrate that autonomous drifting acoustic recorders, combined with environmental sampling and remote satellite data are a powerful tool for studying the habitat dependent distribution of cryptic cetacean species.